Effectiveness of Task Based Language Teaching to Develop Writing Skill at Secondary Level: Teachers’ Perspectives - Gautam, Krishna (Kalika Journal of Multidisciplinary Research, 2026)
English language teaching learning process is shifted from teacher centered to student-centered through the innovative and participatory teaching learning approaches and techniques. Task Based Language Teaching (TBLT) is one of the widely discussed learner-centered techniques that focuses on the completion of tasks on the part of the students. This approach emphasizes on meaningful communication through real-life tasks for enhancing language proficiency. This paper explores the effectiveness of Task-Based Language Teaching (TBLT) in developing students’ writing skills from the perspectives of English language teachers at secondary level in Nepal. Using the qualitative methods, including interviews and classroom observations, this research explores how teachers perceive the implementation of TBLT in EFL instruction, the effectiveness in developing students’ writing skill, challenges they face and some ways to mitigate the challenges. The findings reveal that most of the teachers take TBLT as a powerful approach that encourages students’ engagement in completion of tasks that helps to develop autonomy in learning, creative and critical thinking and real use of language. However, challenges such as limited resources, large size classes, time management, and lack of training for teacher education were also noted. The study concludes that while TBLT is an effective method for developing writing skill on students, its success largely depends on the trained teachers, teachers’ self-motivation, and institutional support.